JOURNEY TO THE CLOUD. - Kunamneni, Venubabu (InSight: Rivier Academic Journal, 2011)
This article gives the basic concept, defines the terms used in the industry, and outlines the general Architecture, SaaS, PaaS and IaaS of Cloud computing. It gives a summary of Cloud Computing and provides a good foundation for understanding of the concepts. Cloud computing is a better way to run your business. Instead of running your apps on your data center, they run on a shared data center.